Chapter 3: Dose-Response Relationships (Principles of Medical Toxicology, 2025)
AuthorMiss Reethu Metilda Manukonda, PG Scholar, Department of Pharmacology, Sri Vasavi Institute of Pharmaceutical Sciences, Tadepalligudem, Andhra Pradesh, IndiaAbstractDose-response relationships represent the cornerstone of toxicological assessment, quantifying how biological systems react to varying exposure levels of toxic substances. These relationships help determine whether effects follow threshold or non-threshold models, with threshold responses occurring only above specific dose levels while non-threshold effects theoretically possible at any exposure. The concept of hormesis—where low doses produce opposite effects from high doses—further complicates these patterns. Toxicologists establish critical reference points including NOAEL (No-Observed-Adverse-Effect Level), LOAEL (Lowest-Observed-Adverse-Effect Level), TD50 (Toxic Dose affecting 50% of population), and LD50 (Lethal Dose for 50%). Safety margins derive from these values through application of uncertainty factors accounting for interspecies differences, human variability, data limitations, and exposure duration. The resulting reference doses and acceptable daily intakes guide regulatory standards and clinical decision-making. Risk assessment integrates these principles through a structured four-stage process: hazard identification, dose-response assessment, exposure assessment, and risk characterization. Individual variations due to genetics, age, health status, and other factors create significant response differences, necessitating population-protective approaches when establishing safety standards for environmental toxins, pharmaceuticals, and occupational exposures.Keywords: Dose-response, Threshold, Risk Assessment, Uncertainty Factors, NOAEL, Reference DoseVIEW PDF